Information system for picket presence of Babinsa Koramil 0827/18 Kangean Island Madura Web-Based - dany Achmaddany ADA (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2025)
Koramil 0827/18 in conducting attendance still uses manual methods such as recording, the abstacles that occur in recording and name of the subject, and in the office must also provide attendance forms in paper form in large quantitles. The web-based attendance information system at Koramil 0827/18 was created with the alm of making the attendance process and reporting Koramil data easier. In this study, the testing method used is using blackbox testing. Programming language using PHP and Mysql storage database. The software development method used is the waterfall method and uses the Codeiniter framework, The system that has been created has been used at the Koramil 0827/18 which is expected to help the process of attendance and reporting of Koramil data to be faster and more accurate